2014
DOI: 10.1002/jcph.288
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and pharmacodynamics of rivaroxaban in patients with non‐valvular atrial fibrillation: Results from ROCKET AF

Abstract: Two once-daily rivaroxaban dosing regimens were compared with warfarin for stroke prevention in patients with non-valvular atrial fibrillation in ROCKET AF: 20 mg for patients with normal/mildly impaired renal function and 15 mg for patients with moderate renal impairment. Rivaroxaban population pharmacokinetic (PK)/pharmacodynamic (PD) modeling data from ROCKET AF patients (n ¼ 161) are reported and are used to confirm established rivaroxaban PK and PK/PD models and to re-estimate values of the models' parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
130
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(156 citation statements)
references
References 28 publications
(74 reference statements)
23
130
2
1
Order By: Relevance
“…We also examined the proportion of patients who had a plasma peak concentration of apixaban, or rivaroxaban below the fifth percentile or plasma peak concentration of dabigatran below the 10th percentile (the lowest percentile reported in the literature for dabigatran);14, 15, 16, 17 the proportion of patients who were switched to warfarin based on the discretion of the treating physician; and the proportion of patients with recurrent VTE and/or stroke during the study follow‐up since the peak concentration was measured. The latter two outcomes were assessed in 22 patients from the anticoagulation clinics.…”
Section: Methodsmentioning
confidence: 99%
“…We also examined the proportion of patients who had a plasma peak concentration of apixaban, or rivaroxaban below the fifth percentile or plasma peak concentration of dabigatran below the 10th percentile (the lowest percentile reported in the literature for dabigatran);14, 15, 16, 17 the proportion of patients who were switched to warfarin based on the discretion of the treating physician; and the proportion of patients with recurrent VTE and/or stroke during the study follow‐up since the peak concentration was measured. The latter two outcomes were assessed in 22 patients from the anticoagulation clinics.…”
Section: Methodsmentioning
confidence: 99%
“…Rivaroxaban has shown to have a consistent anticoagulant effect and safety in the elderly and in patients with lower GFR [41,44]. In the ROCKET-AF trial, given the available pharmacokinetic data on rivaroxaban in patients with deep vein thrombosis [45], researchers established the safety and efficacy of the drug at a reduced dose (15 mg once daily) in patients with an eGFR of 30-49 mL/min [46,47]. In the Re-LY trial, dabigatran has been analyzed in patients with a CrCl higher than 30 mL/min, in two different dosages (110 mg or 150 mg twice daily), but without a specific dosage for kidney impairment [48].…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] A population PK/PD model has been reported for rivaroxaban. 21 In this study, a significant interindividual variability was observed with regard to the baseline value of PT but not the slope for the treatment effect. Therefore, it was possible to extend this model to apixaban and edoxaban by adjusting the slope for the treatment effect based on the prior reports.…”
Section: Population Pk and Pk/pd Modelsmentioning
confidence: 99%
“…27 In addition, PT increases induced by therapeutic concentrations of FXa inhibitor are small, thus variable compared with warfarin. 21 Therefore, in the present analysis, PT ratio, a relative increase of PT from baseline of each patient, was used for the simulation analyses to avoid these difficulties. The detailed procedure of PT estimation is provided in supplemental Methods.…”
Section: Model Analysismentioning
confidence: 99%
See 1 more Smart Citation